2021
DOI: 10.3390/cells10061424
|View full text |Cite
|
Sign up to set email alerts
|

How SARS-CoV-2 and Other Viruses Build an Invasion Route to Hijack the Host Nucleocytoplasmic Trafficking System

Abstract: The host nucleocytoplasmic trafficking system is often hijacked by viruses to accomplish their replication and to suppress the host immune response. Viruses encode many factors that interact with the host nuclear transport receptors (NTRs) and the nucleoporins of the nuclear pore complex (NPC) to access the host nucleus. In this review, we discuss the viral factors and the host factors involved in the nuclear import and export of viral components. As nucleocytoplasmic shuttling is vital for the replication of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 341 publications
(457 reference statements)
0
23
0
Order By: Relevance
“…It is not known if Nsp1 can interfere with these nuclear export proteins. The exact binding interactions are still under investigation [19][20][21][22]. Nsp1 did not impair the RNA-binding ability of NXF1 [5].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is not known if Nsp1 can interfere with these nuclear export proteins. The exact binding interactions are still under investigation [19][20][21][22]. Nsp1 did not impair the RNA-binding ability of NXF1 [5].…”
Section: Introductionmentioning
confidence: 94%
“…The multifunctional Nsp1 protein also disrupts the nuclear mRNA export machinery to inhibit host gene expression by binding directly to the complex of NXF1 and NXT1 [5]. NXF1-NXT1 is the principal factor that mediates docking and translocation of messenger ribonucleoprotein complexes through the nuclear pore complex (NPC) from nucleus to cytoplasm [8,19,20]. NXF1-NXT1 binds the transcription-and-export complex (TREX) that includes THO, UAP56, DDX39B, ALYREF (Aly/REF export factor), and proteins that bind to 5' 7-methylguanosine caps, spliced intron sites, and polyadenine tails of mRNAs [21].…”
Section: Introductionmentioning
confidence: 99%
“…NPCs consist of multiple copies of ∼30 different proteins known as nucleoporins (NUPs). Around one-third of NUPs including NUP62 contain unstructured phenylalanine–glycine (FG) repeats and form a soft and flexible cobweb inside the pore [ [6] , [7] , [8] , [9] ], which establishes conditional partitions. During nuclear transport, cargos require the aid of nuclear transport receptors called karyopherins to pass through the NPCs.…”
Section: Introductionmentioning
confidence: 99%
“…The last contribution examines the pathways used by SARS-CoV-2 and other viruses to invade the host nucleocytoplasmic transport system. Sajidah et al discuss the viral and host factors involved in the nuclear import and export of viral components [47]. The novel human betacoronavirus SARS-CoV-2 has triggered an unprecedented pandemic in the 21st century, and several studies have revealed interactions between SARS-CoV-2 viral proteins and host nucleoporins [48,49].…”
mentioning
confidence: 99%
“…The novel human betacoronavirus SARS-CoV-2 has triggered an unprecedented pandemic in the 21st century, and several studies have revealed interactions between SARS-CoV-2 viral proteins and host nucleoporins [48,49]. As nucleocytoplasmic shuttling is crucial for the replication of many viruses, Sajidah et al also review several drugs that target the host nuclear transport machinery and discuss their feasibility as antiviral treatments [47]. How viral components enter or hijack the NPC undoubtedly requires further exploration.…”
mentioning
confidence: 99%